2016
DOI: 10.1002/pat.3776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeolite and boric acid on epoxy-based composites

Abstract: Epoxy composites filled with boric acid and natural zeolite with different percentage (1, 5, and 10 wt%) were prepared. Hexamethylenediamine and polyethylenpolyamine were used as curing agents. The prepared samples and starting materials were examined using the methods of thermal analysis and scanning electron microscopy. The parameters of thermal decomposition in argon were analyzed. The limiting oxygen index was calculated in accordance with Van Krevelen and Hoftyzer equation. The thermal characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The obtained results revealed that the thermal stability of PHEMA/BA composite hydrogels with the increasing the ratio of BA was improved. In addition, our finding is an agreement with previous studies …”
Section: Resultssupporting
confidence: 94%
“…The obtained results revealed that the thermal stability of PHEMA/BA composite hydrogels with the increasing the ratio of BA was improved. In addition, our finding is an agreement with previous studies …”
Section: Resultssupporting
confidence: 94%
“…When 0.15% of BA was incorporated, T d2% of cross‐linked aerogel increased to 274°C. It suggested that CNF underwent a thermally induced esterification/cross‐linking process, retarding the pyrolysis of CNFs' molecular backbones . However, further increase in BA content decreased the initial decomposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that CNF underwent a thermally induced esterification/cross-linking process, retarding the pyrolysis of CNFs' molecular backbones. 56 However, further increase in BA content decreased the initial decomposition temperature. The T dmax also began to decline when the BA content was higher than 0.45%.…”
Section: Thermal Stabilitymentioning
confidence: 97%
“…Visakh et al studied the effects of different additions of H 3 BO 3 on the fire safety of epoxy resin. They found that the limited oxygen index value increased from 17.6% to 28.1% after adding 10‐wt% H 3 BO 3 , and the thermal stability was significantly improved and more char residue was formed . Uddin explored the effects of boric acid on the flammability and thermal stability of chitosan (CS)/cellulose nanofiber (CNF) composite film.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the limited oxygen index value increased from 17.6% to 28.1% after adding 10-wt% H 3 BO 3 , and the thermal stability was significantly improved and more char residue was formed. 11 Uddin explored the effects of boric acid on the flammability and thermal stability of chitosan (CS)/cellulose nanofiber (CNF) composite film. Their results showed that the addition of boric acid improved the thermal stability of the bicomponent film.…”
mentioning
confidence: 99%